Gambaran ECPT Dan ECPM Penolong Saat Melakukan Resusitasi Jantung Paru - Sari, Putu Ayu Karwina; Saputra, I Kadek; Sawitri, Ni Komang Ari (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 7 No 1 (2021): Volume 7 N0 1 June 2021, 2021)
A good quality of cardio pulmonary resuscitation (CPR) is crucial to success in restoring breath and heart function that has rested. High workload among nurses can cause fatigue and reduce the quality of CPR. The cardiovascular workload the rescuer when performing CPR should be measured, so it can be used to provide recommendation on workload reduction. One measurement of cardiovascular workload is Extra Calorie due to Peripheral Temperature (ECPT) and Extra Calorie due to Peripheral Metabolism (ECPM). However, there were no previous studies has discussed about the ECPT and ECPM among rescuer. This study aims to measure the ECPT and ECPM of rescuer during performing CPR. This was a pre-experimental study with one-shot case study. Sample consisted of 20 students of Nursing Study Program and Professional Nursing, Faculty of Medicine, Udayana University that were selected using purposive sampling technique. After performing CPR for 10 minutes, the students’ recovery rate on the first and fifth minutes were recorded. A univariate analysis was performed, and result showed that the median of ECPT was 22.97 and the median of ECPM was 31.53. The result means that cardiovascular workload during performing CPR at 24 o C is more likely influenced by metabolic processes.